2013
DOI: 10.1093/nar/gkt923
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of the TnaC nascent peptide with rRNA in the exit tunnel enable the ribosome to respond to free tryptophan

Abstract: A transcriptional attenuation mechanism regulates expression of the bacterial tnaCAB operon. This mechanism requires ribosomal arrest induced by the regulatory nascent TnaC peptide in response to free L-tryptophan (L-Trp). In this study we demonstrate, using genetic and biochemical analyses, that in Escherichia coli, TnaC residue I19 and 23S rRNA nucleotide A2058 are essential for the ribosome’s ability to sense free L-Trp. We show that the mutational change A2058U in 23S rRNA reduces the concentration depende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
34
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 43 publications
5
34
0
Order By: Relevance
“…Earlier biochemical studies suggested that the binding site of the free L-Trp may be located directly in the A-site of the PTC and that it may overlap with the binding site of the antibiotic sparsomycin (Cruz-Vera et al, 2006Cruz-Vera and Yanofsky, 2008). However, this view was recently challenged in a careful mutational analysis (Martínez et al, 2014). Indeed, our cryo-EM reconstruction cannot provide any evidence for tryptophan binding within the PTC.…”
Section: Cryo-em Structure Of a Tnac-stalled Ribosomementioning
confidence: 80%
See 2 more Smart Citations
“…Earlier biochemical studies suggested that the binding site of the free L-Trp may be located directly in the A-site of the PTC and that it may overlap with the binding site of the antibiotic sparsomycin (Cruz-Vera et al, 2006Cruz-Vera and Yanofsky, 2008). However, this view was recently challenged in a careful mutational analysis (Martínez et al, 2014). Indeed, our cryo-EM reconstruction cannot provide any evidence for tryptophan binding within the PTC.…”
Section: Cryo-em Structure Of a Tnac-stalled Ribosomementioning
confidence: 80%
“…Consistent with the composition of these binding pockets, mutation of U2609 and A752 and mutations of A2058 have been shown to severely reduce the efficiency of TnaC stalling (Cruz-Vera et al, 2005;Cruz-Vera and Yanofsky, 2008;Gong and Yanofsky, 2002). Moreover, mutation of I19 of the TnaC peptide to amino acids other than the chemically very similar leucine also affects stalling (Martínez et al, 2014). Although distinct density enabled the majority of side chains in the TnaC nascent peptide to be assigned, I19 and I15 lack a clearly defined conformation.…”
Section: Interactions Of Tnac With Components Of the Ribosomal Tunnelmentioning
confidence: 83%
See 1 more Smart Citation
“…In this model, slow translation of CGA codons closer to the initiation site (in which stalled ribosomes would directly affect the next initiating ribosome) would be more inhibitory than slow translation further from the initiation site; a feedback mechanism of this type would be independent of Asc1 protein and might only operate near the initiation site. The second model is based on the idea that the efficiency of the peptidyl transferase reaction is modulated by the nascent polypeptide within the exit tunnel, an idea for which there is precedent from nascent peptide sequences that stall the ribosome (Ramu et al 2011;Martinez et al 2014), and evidence for contact between the nascent polypeptide and 28S rRNA at the peptidyl transferase center (Bhushan et al 2010). In this model, which is similar to the promoter clearance step in transcription, the ribosome becomes committed to continued elongation as the exit tunnel fills, and thus CGA codons become less inhibitory as the exit tunnel fills.…”
Section: Discussionmentioning
confidence: 99%
“…Because the active localization reaction cancels the elongation arrest, their arrest propensity is inversely correlated with the cellular activity of the respective translocation machinery; this allows them to compensate for the loss of activity of the cellular machinery by upregulating the synthesis of the core component of the machinery. Another regulatory nascent polypeptide, TnaC, undergoes termination arrest in response to increased concentration of tryptophan (Martinez et al 2013). The arrested ribosome then interferes with recruitment of the transcription termination factor ρ onto the mRNA and, consequently, enhances transcription of the target gene encoding tryptophanase (Chap.…”
Section: Regulatory Nascent Polypeptides Monitor and Control Cellularmentioning
confidence: 99%